The Ethics of Psychological Artificial Intelligence: Clinical Considerations. Issue 2 (1st October 2021) - Fulmer, Russell; Davis, Tonya; Costello, Cori; Joerin, Angela
Abstract : Psychological artificial intelligence has a growing research base but often overlooks ethical considerations. Drawing from a review of the literature, the experiences of three counselor educators, and an industry insider, this article names six issues relevant to psychological artificial intelligence. The clinical implications of each issue are discussed, some at the national level, some at the practice level. Suggestions for the counseling profession, with an emphasis on prevention, are offered.